ANALISA PENGARUH PENGELASAN LISTRIK TERHADAP SIFAT MEKANIK BAJA KARBON RENDAH DAN BAJA KARBON TINGGI - Gunawan, Yuspian; Endriatno, Nanang; Anggara, Bayu Hari (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The process welding which in principle is connecting two or more components, more rightly aimed toassemble ( assembly ) several components into one form of machine. The purpose of this research is to findthe mechanical force low carbon steel and high carbon steel. Material of this research is low carbon steelplate thick of 10 mm and high carbon steel of a spring thick 10 mm. the process welding use electrodesE6013 and E7016 by the angle v . Test in do is testing pull and testing hardness brinell .Where testing pull ,tensile strength on the highest low carbon steel found in specimens 2 namely 44,92 kg/mm2 .While in testingpul high carbon steel tensile strength is highest in specimens column material that is 91,35 kg /mm2. ForBrinell Hardness Test, the highest hardness HAZ to low carbon steel is on a point of 1 and 3 namely 104,53kg/ mm2. While highest hardness HAZ to high carbon steel is at that point 1 namely 201,03 kg / mm2.Keywords: welding, tensile strength and hardness